ANU GRACE Data Analysis: Orbit Modeling, Regularization and Inter‐satellite Range Acceleration Observations. Issue 2 (23rd February 2022) - Allgeyer, S.; Tregoning, P.; McQueen, H.; McClusky, S. C.; Potter, E.‐K.; Pfeffer, J.; McGirr, R.; Purcell, A. P.; Herring, T. A.; Montillet, J.‐P.
Abstract: Several different basis functions have been used to represent the Earth's gravity field in order to generate estimates of mass variations on Earth from the analysis of data of the Gravity Recovery and Climate Experiment (grace ) and its successor grace Follow‐On missions, including spherical harmonics, mass concentration elements (mascons) and slepian functions. Each approach depends inherently upon accurate modeling of the orbits of the pair of satellites as they revolve around the Earth, so that the observations of inter‐satellite changes in range (or, more specifically, range rate) can be exploited to identify mass variations. We have developed software using a classical orbit modeling approach, mascons and 24‐hr orbit integration, to estimate simultaneously corrections to orbital parameters and the temporal gravity field from grace data. Rather than using the range rate, we use the range acceleration as the inter‐satellite observable as it aids in localizing the mass variations. Level‐1 B range acceleration observations contain high levels of high‐frequency noise that inhibits their usefulness for this purpose. Instead, we generate range acceleration observations by numerical differentiation of the Level‐1B range rate prefit residuals. Simulations show that the gravity signal is not attenuated in this process. Our monthly estimates of mass anomalies from grace data (2003–2016) agree well with previous studies, both spatially and temporally. When converted to spherical harmonics our time series of C 2, 0, derived from grace data alone, are close to the independent estimates from satellite laser ranging, but the overall solution is improved by substituting the SLR C 2, 0 . Plain Language Summary: The Gravity Recovery and Climate Experiment (grace ) space gravity mission consists of a pair of identical twin satellites one following the other and separated by about 200 km. The distance between the satellites is altered by mass distribution on Earth. While all published temporal gravity field models are estimated from the rate of change of the inter‐satellite distances (known as range rate), this study uses the relative acceleration (known as range acceleration) between the satellites as the observation to determine the distribution of mass on Earth. The methodology we developed has multiple advantages with respect to solutions derived using the range rate. Mass changes on Earth are located spatially with greater accuracy and have a better resolution of the long wavelength gravity field. Key Points: Mass anomalies are derived from GRACE inter‐satellite range acceleration observations High levels of high‐frequency noise present in the Level‐1B range acceleration observation can be mitigated with appropriate pre‐processing Our solutions on major ice sheets, the Amazon basin and over oceans derived with the range acceleration agree with other processing centers